2015
DOI: 10.1007/s00423-015-1303-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after thyroid surgery, insignificant or still an issue?

Abstract: Death after thyroidectomy is very uncommon, and most often results from a combination of advanced age, giant goiters, and upper airway complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…[5][6][7] Complications in thyroid surgery can be reduced by proper anatomical knowledge of the neck and using precise surgical technique. 8,9 In the last 40 years there are only a few publications in the literature about the use of microsurgery in thyroid surgery, and all emphasize the concept that microsurgery improves surgical results especially in reinterventions and in lymphadenectomy.…”
mentioning
confidence: 99%
“…[5][6][7] Complications in thyroid surgery can be reduced by proper anatomical knowledge of the neck and using precise surgical technique. 8,9 In the last 40 years there are only a few publications in the literature about the use of microsurgery in thyroid surgery, and all emphasize the concept that microsurgery improves surgical results especially in reinterventions and in lymphadenectomy.…”
mentioning
confidence: 99%
“…Its incidence and mortality has not been described in the literature. To date, there are only 11 cases of GAS infection after thyroidectomy reported in the literature (Table 1) [1,[10][11][12][13][14][15], and many of these cases were complicated by septic shock and death despite early systemic antibiotic treatment. However, there are no cases with GAS infection secondary to tracheal perforation, as we present here.…”
Section: Discussionmentioning
confidence: 99%
“…T he overall complication rate after thyroid surgery is less than 5%, which is primarily associated with airway complications in big goiters. A recent publication showed that mortality after thyroidectomy is 0.06%, and only 10% is caused by sepsis [1].…”
mentioning
confidence: 99%
“…Thyroid surgery is considered a relatively safe procedure (mortality rate: 0.065%) [5]. However, various complications are associated with neck dissections.…”
Section: Discussionmentioning
confidence: 99%